2014
DOI: 10.1186/1472-6920-14-130
|View full text |Cite
|
Sign up to set email alerts
|

Study motives, career choices and interest in paediatric dentistry among final year dental students in Nigeria

Abstract: BackgroundStudents’ motives for studying Dentistry have been a subject of interest for years because of the potential for understanding the psychological makeup and subsequent job satisfaction for the dentist. It is also useful in identifying expectations of the profession. This study therefore tried to identify study motives and career preferences of dental students especially with respect to the practice of paediatric dentistry.MethodsThis was a cross-sectional study using a self-administered questionnaire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 23 publications
3
21
1
1
Order By: Relevance
“…Our data showed that 37% of the dental students and 30% of the dental hygiene students had a family member in dentistry or in dental hygiene; however, students with such family members did not differ overall in their career choice motivations from students without such family backgrounds. In the past, studies clearly showed that students chose their career because they were inspired by others in choosing dentistry [14][15][16]18,20,[29][30][31][32][33] or dental hygiene. [22][23][24][25][26][27] However, being inspired by others might differ from being inspired by a close family member in the profession.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data showed that 37% of the dental students and 30% of the dental hygiene students had a family member in dentistry or in dental hygiene; however, students with such family members did not differ overall in their career choice motivations from students without such family backgrounds. In the past, studies clearly showed that students chose their career because they were inspired by others in choosing dentistry [14][15][16]18,20,[29][30][31][32][33] or dental hygiene. [22][23][24][25][26][27] However, being inspired by others might differ from being inspired by a close family member in the profession.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, studies clearly showed that students chose their career because they were inspired by others in choosing dentistry [14][15][16]18,20,[29][30][31][32][33] or dental hygiene. In the past, studies clearly showed that students chose their career because they were inspired by others in choosing dentistry [14][15][16]18,20,[29][30][31][32][33] or dental hygiene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants for this study were consenting final year physiotherapy students in all physiotherapy training institutions in the South Western region of Nigeria namely; (13). Domains relevant to the present study were identified in the original questionnaire and used for developing the questionnaire for this study.…”
Section: Participantsmentioning
confidence: 99%
“…The factors influencing the choice of a dental profession are very important in terms of identifying the expectations of the profession. 1 Several studies have reported that the majority of the undergraduate dental students prefer to continue their education toward a specialty degree. [2][3][4] This has important implications for the dental workforce planning agenda in any country.…”
Section: Introductionmentioning
confidence: 99%